Utilization of interactive learning multimedia through the canva application in Islamic religious education subjects in class XI RPL SMK Wirajaya Tanjung Morawa - Luthfiah Khairani Nasution; Amini Amini (Lembaga Riset Mutiara Akbar, 2026)
This study aims to describe the use of interactive learning multimedia through the Canva application in Islamic Religious Education (PAI) subjects for grade XI RPL at SMK Wirajaya Tanjung Morawa in the 2025/2026 academic year. This study used a qualitative method with a descriptive approach. The research subjects consisted of PAI teachers and grade XI RPL students. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis included data condensation, data presentation, and conclusion drawing. The results showed that the use of the Canva application as interactive learning multimedia can increase student interest and activeness in the learning process, thereby creating a more engaging learning atmosphere that helps students better understand PAI material. Canva media facilitates teachers in delivering and presenting material and creates a more visual, systematic, and varied learning experience. Therefore, the use of interactive learning multimedia through the Canva application can be used as an alternative, innovative, relevant, and effective learning medium for implementation in Islamic Religious Education learning at the vocational high school level.